As estratégias de tutoramento em livros didáticos de português língua estrangeira - Braida, Fabrícia Cavichioli (Linguagens & Cidadania, 2017)
This paper has the aim of presenting the partial results obtained from the analysis of didactic materials as genres to the teaching of Portuguese as a Second Language (PSL). In order to achieve this goal, this study investigates: 1º) what are the tutorial strategies the teacher’s book presents to help both teacher and student’s performance; 2º) what is the design presented in the tutorial of reading activities in the student’s book. The didactic materials analyses will be based on the Activity Theory (Leontiev). The partial results suggest the teacher’s book do not significantly provide scaffolding neither to the teacher nor to the students’ strategies, that is, it just gives some suggestion to the teacher. On the other hand, in the students’ book, the absence of tutorials was identified.